(untitled) (Research, Society and Development, 2017)
The business environment is permeated by uncertainty and volatility, making the activities related to the ever-challenging decision making for administrators. In the current context, it is fundamental premise for continuous evaluation of the assets applied in the organizations, be they of any segment or size. This article aims to evaluate the financial performance of companies in a simulated environment in business games by Analytic Hierarchy Process (AHP) using as a base the analysis of current liquidity ratios, profitability and apital structure, demonstrating, through these indices, the industry involved in the game that obtained the best performance.